2016
DOI: 10.1109/jlt.2016.2601122
|View full text |Cite
|
Sign up to set email alerts
|

Fibre Bragg Grating-Based Acoustic Sensor Array for Improved Condition Monitoring of Marine Lifting Surfaces

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent repository link:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…In marine applications, simulated AE signals have previously been measured on a submerged steel half rudder blade. Measurement and localisation of an AE source was performed while comparing different sensor types [29]. Furthermore, AE investigations on composite tidal turbine blades are emerging [30].…”
Section: Introductionmentioning
confidence: 99%
“…In marine applications, simulated AE signals have previously been measured on a submerged steel half rudder blade. Measurement and localisation of an AE source was performed while comparing different sensor types [29]. Furthermore, AE investigations on composite tidal turbine blades are emerging [30].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to traditional capacitive or piezoelectric acoustic sensors, optical fiber acoustic sensor has unique advantages, such as passive, corrosion resistant, light weight, freedom from the interference of electromagnetic irradiation, and multiplexing capability [1][2][3][4] . A variety of fiber optic acoustic sensors have been demonstrated over the past decades, including Fiber Bragg grating (FBG) [5,6] ,…”
Section: Introductionmentioning
confidence: 99%
“…In order to improve the responsivity of FBGs at very low-pressure levels, Moccia et al used a ring-shaped polymer's coating and demonstrated a microphone with a minimum detectable acoustic signal of about 10 mPa Hz −1 [17]. The excellent multiplexing capability of the FBG based microphones has been effectively utilized for condition monitoring of marine lifting surfaces and also for crack monitoring in historical masonry [18,19]. However, the requirement of temperature compensation techniques and the sophisticated fabrication process increases the complexity of the sensor and its cost as well.…”
Section: Introductionmentioning
confidence: 99%